Perspectivas e metodologias de pesquisa da Comunicação Social no contexto da internet com o Big Data e da especialização Data Scientist - Gonçalves, Leandro Tavares (2014)
The work analyzes the media in the context of the Internet and outlines new methodologies for the study area in filtering meanings in the scientific realm of information flows from social networks, news media or any other device that allows storage and retrieval of structured information and unstructured. In an attempt to reflect on the ways that these information flows and develop mainly in the volume produced, the project scales the fields of meanings that this relationship appears in the theories and practices of research. The aim of this study is to contextualize the media area within a changing and dynamic reality that is the environment of the internet and make parallel before the applications already successful in other areas. With the method of case study three cases were analyzed under two conceptual keys to Web Sphere Analysis and the Web Science reflecting the opposing information systems in the discursive and structural aspect. This way observes what the Media has earned in order to view its objects of study in the environment of internet networks for these prospects. The research result shows that it is a challenge to the researcher Media seek new learning, but the feedback information in a collaborative environment that the Internet presents is fertile ground for research path, for data modeling wins analytical corpus when the set of tools promoted and driven by technology allows isolating contents and allows deepening the meanings and relationships.